Analysis of Specific Legal and Trade-related Issues in a Possible PH-EU Economic Partnership: The Philippine Constitution, Competition Policy, Government Procurement, Intellectual Property Rights, Dispute Settlement, and Trade Remedies - Lai-Lynn Angelica B. Barcenas (Philippine Institute for Development Studies (PIDS), 2015)
This paper provides an overview of the Philippines' defensive and offensive interests in a free trade agreement with the European Union in the areas of competition policy, government procurement, intellectual property rights, dispute settlement, and trade remedies. It examines these interests in accordance with the mandate of the Philippine Constitution, and the Philippine position vis-a-vis the goals and strategies of the European Union with respect to its trade relations with its trading partners.
Keywords: 330; Philippines-EU free trade agreement; trade negotiations; Philippine Constitution; competition; government procurement; intellectual property rights; dispute settlement; anti-dumping; countervailing measures; safeguards